Safety and Immunogenicity of Zoster Vaccine Live in Human Immunodeficiency Virus–Infected Adults With CD4+ Cell Counts >200 Cells/mL Virologically Suppressed on Antiretroviral Therapy. (26th March 2018) - Benson, Constance A; Andersen, Janet W; Macatangay, Bernard J C; Mailliard, Robbie B; Rinaldo, Charles R; Read, Sarah; Bozzolo, Dawn R; Purdue, Lynette; Jennings, Cheryl; Keefer, Michael C; Glesby, Marshall; Tebas, Pablo; et al.
Abstract : Live attenuated herpes zoster vaccine administered to HIV-infected adults suppressed on antiretroviral therapy with CD4 + counts ≥200 cells/µL was generally safe and immunogenic. Antibody responses were similar to those observed in older adults without HIV infection who received the same vaccine. Abstract: Background: Herpes zoster (HZ) risk is increased in human immunodeficiency virus (HIV)–infected persons. Live attenuated zoster vaccine (ZV) reduces HZ incidence and severity in adults; safety and immunogenicity data in HIV-infected adults are limited. Methods: We conducted a randomized, double-blind, placebo-controlled trial in HIV-infected adults virally suppressed on antiretroviral therapy (ART). Participants, stratified by CD4 + count (200–349 or ≥350 cells/µL), were randomized 3:1 to receive ZV or placebo on day 0 and week 6. The primary endpoint was serious adverse event or grade 3/4 signs/symptoms within 6 weeks after each dose. Immunogenicity (varicella zoster virus [VZV]–specific glycoprotein enzyme-linked immunosorbent assay and interferon-γ enzyme-linked immunospot assay responses) was assessed at 6 and 12 weeks postvaccination. Results: Of 395 participants (296 ZV vs 99 placebo), 84% were male, 47% white, 29% black, and 22% Hispanic; median age was 49 years. Safety endpoints occurred in 15 ZV and 2 placebo recipients (5.1% [95% confidence interval CI, 2.9%–8.2%] vs 2.1% [95% CI, .3%–7.3%]; P = .26). Injection site reactions occurred in 42% of ZV (95% CI, 36.3%–47.9%) vs 12.4% of placebo recipients (95% CI, 6.6%–20.6%) ( P < .001). Week 12 median natural log VZV antibody titer was higher for ZV (6.30 [Q1, Q3, 5.64, 6.96]) vs placebo (5.48 [Q1, Q3, 4.63, 6.44]; P < .001) overall and in the high CD4 + stratum ( P = .003). VZV antibody titers were similar after 1 or 2 ZV doses. Polymerase chain reaction–confirmed HZ occurred in 2 participants (1 ZV; 1 placebo); none was vaccine strain related. Conclusions: Two doses of ZV in HIV-infected adults suppressed on ART with CD4 + counts ≥200 cells/µL were safe and immunogenic. Clinical Trials Registration: NCT00851786.